Rol de la enfermería para el afrontamiento emocional en el paciente oncológico con cuidados paliativos - Calderón Camacho, Karina Estefanía (2025)
Introduction: In oncologic palliative care, nursing intervenes in a fundamental way in the emotional coping of the patient, taking into account not only their physical requirements, but also their emotional, psychological and social dimensions. Objective: To determine the role of the nurse in the emotional coping of the oncologic patient with palliative care. Materials and Methods: The study was a non-experimental descriptive study, through a narrative review supported by a bibliographic review, complying with PRISMA standards. Databases such as Scielo, Google Scholar, PubMed, among others, were consulted. From a total of 65 publications, 45 were excluded and 20 more recent studies were selected. Results: The palliative care nurse is necessary to provide comprehensive care to the patient; not only does he/she perform physical care but also provides emotional and spiritual care in some cases to patients and family members. However, it has a high emotional intensity due to the constant exposure to suffering and death, which shows what are the constant training needs in addition to having a way to cope with these situations. Conclusions: Nurses in the palliative care of patients, offer physical help and emotional support encouraging resilience and a fighting spirit. However, the emotional amount of this task can harm their health and cause them to leave the field without adequate stress management, however, it is imperative to establish training aids and tactics that strengthen endurance capabilities.